2020
DOI: 10.3390/ijms21020463
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Autoantibodies to Insulin-Like Growth Factor-1 Receptor Associate with Poor Physical Strength

Abstract: Natural autoantibodies to the IGF1 receptor (IGF1R-aAb) have been described in relation to Graves’ ophthalmopathy. Other physiological roles of natural IGF1R-aAb are not known. We hypothesized that IGF1R-aAb may be related to muscle development. Serum samples (n = 408) from young overweight subjects (n = 143) were collected during a lifestyle intervention study. Anthropometric parameters, along with leptin, IGF1 and IGF1R-aAb concentrations, were analyzed, and the subjects were categorized into positive or neg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Using the same technique of constructing an antigen receptor fusion protein with luciferase as reporter at the intracellular C-terminus, we identified around 10% of subjects positive for aAb to the IGF1-receptor (IGF1R-aAb) [ 28 ]. The IGF1R-aAb proved to inhibit growth hormone signaling and proliferation in vitro [ 28 ], and were associated with low muscle strength in adolescent subjects [ 35 ]. Due to the very small number of positive samples identified in the current study, a similar analysis on a potential physiological role of natural GnRH-R-aAb is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same technique of constructing an antigen receptor fusion protein with luciferase as reporter at the intracellular C-terminus, we identified around 10% of subjects positive for aAb to the IGF1-receptor (IGF1R-aAb) [ 28 ]. The IGF1R-aAb proved to inhibit growth hormone signaling and proliferation in vitro [ 28 ], and were associated with low muscle strength in adolescent subjects [ 35 ]. Due to the very small number of positive samples identified in the current study, a similar analysis on a potential physiological role of natural GnRH-R-aAb is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, therapeutic measures have been improved, and disease severity can successfully be controlled by pharmacological intervention [52]. We have recently studied aAb to the IGF1-receptor (IGF1R), impairing IGF1 signalling [18], and related the presence of IGF1R-aAb to poor physical strength in young subjects [20]. Additional physiological effects are likely, given the broad relevance of IGF1 in development and disease.…”
Section: Discussionmentioning
confidence: 99%
“…The open reading frames encoding human MCT8 and human MCT10, respectively, were amplified by PCR and fused in frame to a firefly luciferase gene (Luc), essentially as described [18][19][20]. The resulting composite reading frame was inserted into the expression vector pIRESneo, generating the expression vectors pIRESneo-MCT8-Luc and pIRESneo-MCT10-Luc, respectively.…”
Section: Construction Of Mct8 and Mct10 Luciferase Fusion Proteins Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the authors of two other studies measuring IGF1R phosphorylation as an indication of direct IGF1R activation by GO-Igs found only very small levels of phosphorylation, although one group concluded that there was no evidence of stimulating IGF1RAbs [12], whereas the other concluded that there may be evidence that a subset of GO patients express stimulating IGF1RAbs [13]. Similarly, Schwiebert et al [40] found naturally occurring IGF1RAbs in young, overweight children, however, these IGF1RAb were antagonists not stimulators.…”
Section: Evidence That Go-igs Activate Tshr/igf1r Crosstalk Via Bindimentioning
confidence: 97%